2009
DOI: 10.1243/09544100jaero387
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and numerical aspects of simulating unsteady flows around the X-31 configuration

Abstract: A symposium was held in 2003 at the University of Glasgow to celebrate the career of Professor Bryan Richards. Professor Richards was a pioneer in conducting integrated computational/experimental aerodynamic studies, and the symposium organizers took his research approach as their theme. The original (and continuing) purposes of the symposium are reproduced here because they are so essential to the overall approach of the meetings. CFD practitioners and experimentalists have a common goal of understanding aero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…Several publications [17,21,35] of the author are used for the validation of the numerical method and grid generation approach and provide the validation for the RANS solver DLR TAU to justify the present numerical approach.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several publications [17,21,35] of the author are used for the validation of the numerical method and grid generation approach and provide the validation for the RANS solver DLR TAU to justify the present numerical approach.…”
Section: Discussionmentioning
confidence: 99%
“…The experimental results are documented by Rein et al [18]. The numerical results using TAU are described in detail in Schütte et al [19][20][21][22][23]. Additional results are given by Boelens [24] and Jirasek and Cummings [25].…”
mentioning
confidence: 99%
“…Most of the applications of the Tau-Code in this paper are based on these experiences. Among others, these computational results include work on the VFE-2 [9] configuration, the X-31 [25][26][27], and the F-16 Cranked Arrow Wing Aerodynamics Project International (CAWAPI) [28].…”
Section: A Computational Fluid Dynamics Solver Taumentioning
confidence: 99%
“…Many research efforts have been reported in the literature to estimate the parameter deviation [19]. In practice, a suitable aerodynamic design of the interceptor that can adaptively respond to the abrupt changes in direction and attitude during flight needs to be incorporated [20]. The OGL in this research is obtained based on linear approximations of the motion equation.…”
Section: Miscellaneousmentioning
confidence: 99%